INOVASI DALAM KOMPETISI: USAHA KULINER LOKAL MENCIPTAKAN KEUNGGULAN KOMPETITIF DI UBUD - Diah Sastri Pitanatri, Putu (Jurnal Master Pariwisata (JUMPA); Volume 03, Nomor 01, Juli 2016, 2016)
Esteemed for its culture, Ubud has developed its image as culinary destination in Bali. The creation of this new branding of Ubud is attached to the dedication of its local talents who consistently serves Balinese food to tourists. Seeing these ongoing developments, this study analyzes the following aspects (1) Ubud and it’s development as culinary destination, (2) innovation showed by local culinary talents, and (3) thin line between cultural enrichment and deprivation. Using critical qualitative, this research was conducted by implementing indepth interviews to selected interviewes.Theories used are cultural tourism and sustainable tourism approaching to related aspects such as experience economy, millennial generation; community based tourism, and invented tradition. Results of this study are (1) the development of Ubud as culinary destination in Bali is not only supported by changes in tourist’s motivation but also the ability of it’s local talents to productively innovate (2) innovation in products, promotions and experiences are the keys in promoting sustainability of these local businesses, and (3) the growth of local culinary enrich cultural experience and is proven to strengthening Ubud’s image as a cultural tourism destination.